Assessment of Kwara state tractor hiring unit (2010)
A survey was undertaken to assess the Kwara State Tractor Hiring Unit using fleet of equipment, personnel and workshop facilities, and its impact on the farming populace in the state as assessment criteria. The study adopted the use of a questionnaire and interview schedules, focused group discussion and personal observation for data collection. Records available at the headquarters of the unit provided additional source of information. The unit has a total of 38 tractors which comprises of 29 Ursus 5312, six New Holland 5635, three heavy duty tractors, 22 disc ploughs, seven mouldboard ploughs, 18 disc harrows, eight disc ridgers, 10 trailers, two rice shellers, five multipurpose shellers, two maize shellers and one fourwheel drive jeep car. Majority (81%) of the equipment were functional, a few (13%) required minor repairs to be used on the farm and 6% were scraps. The unit has neither a workshop nor an implement shed thus exposing the machinery to inclement weather. Personnel in the unit are adequate but the maintenance culture is service driven. There has been a general increase in farm sizes since the introduction of the unit even though only a few farmers have been able to access the services rendered by the unit. Several reasons accounted for the limited beneficiaries from the activities of the unit prominent among which are inability to raise the cost of hiring, delay in service delivery, remoteness of farms and small holdings.The unit has great potentials for improving the agricultural productivity of the state if the equipment available can be effectively utilized. Towards achieving this, it is recommended that a functional workshop and implement sheds be provided at the headquarters and area offices, the activities should be decentralized while adopting a regular maintenance culture. As an agency of the government, there should be adequate funding by the state government.